Pengaruh Return On Asset Terhadap Pertumbuhan Laba pada PT Astra Internasional Tbk (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of Return on Assets (ROA) on profit growth at PT Astra International Tbk. The background of this study is based on the fluctuation of the company's net profit and total assets in the period 2014–2023, particularly the significant decline in 2015, 2019, and 2020. This study uses a quantitative method with an associative approach. The data used are the financial statements of PT Astra International Tbk obtained from the company's official website. The research sample was taken for 10 years (2014–2023) with a purposive sampling technique. Data analysis uses simple linear regression, correlation coefficient test, determination test, and t-test. The results show that ROA has a positive and significant effect on profit growth, with a regression coefficient value of 0.033 and a significance level of 0.017 <0.05. The coefficient of determination (R²) of 52.8% indicates that ROA is able to explain the profit growth variable, while the remaining 47.2% is influenced by other factors outside this study. Thus, the better the company's asset management, the greater the profit growth that can be achieved.